Pengaruh Terapi Hipnosis 5 Jari terhadap Penurunan Nyeri pada Pasien Apendicitis RSI Sultan Agung Semarang - Eka Aprilia Diah Syafitri; Erna Melastuti; Indah Sri Wahyuningsih (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Appendicitis is an inflammatory condition of the small intestinal tract that is about 4 inches in size and located at the end of the secum. This condition often causes significant pain and requires effective management. In addition to pharmacological approaches, non-pharmacological methods such as relaxation techniques and alternative therapies are beginning to be widely applied to reduce pain and anxiety. One promising method is 5-finger hypnosis therapy, which is a relaxation technique that harnesses the power of the mind to achieve calmness and reduce the perception of pain. This study aims to determine the effect of 5-finger hypnosis therapy on pain reduction in appendicitis patients at RSI Sultan Agung Semarang. The research design used was quasi-experimental with a pre-posttest one group approach. A total of 32 appendicitis patients were selected as samples using the total sampling technique. Pain scales were measured before and after the intervention, then analyzed using the Wilcoxon Signed Ranks Test. The results showed a Z-value of -3.097 and a p-value of 0.002 (p < 0.05), indicating a significant difference between pain levels before and after therapy. These findings prove that 5-finger hypnosis therapy is effective in reducing pain in appendicitis patients. This study recommends the application of 5-finger hypnosis therapy as a non-pharmacological approach that can support patient comfort and accelerate the recovery process holistically.